Martin Codax: a história que a música conta - Manuel Pedro Ferreira (Medievalista)
The songs by Martin Codax have been interpreted according to different, often incompatible, perspectives. The author discusses the most recent and relevant contributions, namely by William Paden. Then he tries to ascertain which musical traits in these cantigas might point to an earlier style of women's song symbolized by the “boyfriend” and related keywords. After invoking the impact of gender studies on the interpretation of the cantiga de amigo, as evaluated by Alan Deyermond, the author presents and discusses the different views on the style of the melodies voiced since their discovery a century ago. An excursus explores differences between cantigas II and III and the remaining, and the metrics of the latter, with reference to a recent work by Stephen Parkinson and Rip Cohen; a new musical edition is proposed for these two (and also, in passing, for cantiga V). Finally, those stylistic aspects that in the Vindel MS may betray an earlier tradition, in contrast to those that can be attributed to the artistic initiative of Galician jongleurs, are tentatively identified.